LANGUAGE TEACHER IDENTITY CONSTRUCTION OF FOREIGN LANGUAGE TEACHING ASSISTANTS - Peker, Hilal; Torlak, Metin; Toprak-Çelen, Esma; Eren, Gamze; Günsan, Meral (International Online Journal of Education and Teaching, 2020)
Language teacher identity has been studied in several contexts in English Language Teaching (ELT) field; however, looking at language teacher identity in a United States context in which teachers from other countries teach their native languages as a foreign language has been a rare topic so far. Therefore, this phenomenological qualitative study investigated the lived experiences of four foreign language teaching assistants who lived and taught in the United States through Fulbright Foreign Language Teaching Assistant (FLTA) Program. The findings indicated four main emerging themes: (a) pedagogical shift, (b) cross-cultural awareness, (c) challenges, and (d) goals and expectations. These dynamic components shaped language teachers’ identity in this context. The results are presented under the framework of language teacher identity. Implications as a guide for future FLTA teachers and for teacher exchange programs are provided.